Development of communicative competence of non-linguistic students in the process of foreign language teaching - Mariya P. Kozyreva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article considers the means of developing communicative competence of non-linguistic students in the process of studying foreign languages. Active methods: situational dialogues, computer presentations, role and business games are proved to be effective for the development of students’ communicative skills. The examples of active methods used in foreign language classes for students of different non-linguistic directions of professional training are provided in the article.